Comparative analysis of students' mathematical problem-solving performance in sequential and concurrent multitasking: Evidence from large-scale computer-based tests - Nisa, Titin Faridatun; Budayasa, I Ketut; Lukito, Agung (Edelweiss Applied Science and Technology, 2025)
The integration of digital technology in mathematics education has expanded learning opportunities while simultaneously introducing multitasking demands that may impact student performance. Despite substantial research on the negative effects of multitasking, large-scale empirical evidence comparing sequential and concurrent multitasking within mathematical problem-solving contexts remains limited. This study aims to examine and compare the effects of sequential and concurrent multitasking on students' mathematical problem-solving performance using extensive computer-based assessment data. A quantitative, comparative, ex-post-facto design was employed, analyzing 21,484 student responses from digital mathematics assessments. Performance metrics included accuracy rates, response times, and task viewing times across two multitasking conditions. Results showed that concurrent multitasking demonstrated superior performance across all measured indicators: higher accuracy (18.6% vs. 17.7%), faster response times (110.4 vs. 172.6 seconds), and shorter viewing times (119.1 vs. 191.9 seconds) compared to sequential multitasking. Sequential multitasking required 56.3% longer response times, indicating high task-switching costs. These findings challenge conventional assumptions about the detrimental effects of concurrent multitasking in educational contexts. For digital education, the results suggest that interface designs supporting concurrent problem access may enhance learning efficiency by reducing cognitive overhead associated with task switching. Educational technology developers should consider implementing concurrent presentation formats for related mathematical problems rather than enforcing sequential processing approaches.